2014
DOI: 10.1074/jbc.m113.541573
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Syndecan-1 Induces a Pro-inflammatory Phenotype in Endothelial Cells with a Dysregulated Response to Atheroprotective Flow

Abstract: Background:The endothelial glycocalyx extends into the arterial lumen and experiences shear forces from blood flow. Results:The loss of syndecan-1 results in a pro-inflammatory phenotype in endothelial cells with an altered response to atheroprotective flow. Conclusion: Syndecan-1 plays an important role in maintaining healthy endothelial phenotype. Significance: Therapies that retain syndecan-1 on endothelial cells may have the potential to reduce the progression of vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 60 publications
4
117
0
Order By: Relevance
“…In addition, glycocalyx HSPGs are expressed at higher levels in vascular areas subjected to laminar shear stress, which is known to impart atherosclerosis resistance, than in regions of disturbed flow (43). Recent knockdown studies have indicated that both syndecan-1 and -4 HSPGs are critical in the flow-induced protection of ECs (44,45). In this light, signaling through the TMEM184A heparin receptor provides one mechanism by which HS levels would elicit cellular change during the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, glycocalyx HSPGs are expressed at higher levels in vascular areas subjected to laminar shear stress, which is known to impart atherosclerosis resistance, than in regions of disturbed flow (43). Recent knockdown studies have indicated that both syndecan-1 and -4 HSPGs are critical in the flow-induced protection of ECs (44,45). In this light, signaling through the TMEM184A heparin receptor provides one mechanism by which HS levels would elicit cellular change during the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that EC HSPGs are involved in EC remodeling in response to shear stress (51). In fact, knocking down synde-can-1 or -4 decreases the laminar shear stress protection of endothelial layers from inflammatory damage (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased shedding of the syndecan-1 ectodomain by ADAM17 may aggravate the vascular phenotype in active AAV. 36 Membrane localization of ADAM17 is a prerequisite for its proper function. 37,38 Therefore, we speculated that ADAM17-specific activity in the blood samples of patients with AAV depends on its localization on cell-derived microparticles.…”
Section: Discussionmentioning
confidence: 99%